Personalisierte Gliomtherapie = Personalized therapy for gliomas - Wick, Wolfgang; Hau, Peter (Der Nervenarzt, 2015)
SummaryCurrent therapies for patients with malignant gliomas are starting to integrate molecular factors and age. Nonetheless, these therapies are still not sufficiently individualized. Some positive examples of transfer from basic science to clinical application are currently integrated into the standard treatment and guidelines. These are mainly genetic and other molecular factors that improve diagnosis and classification of gliomas and markers supporting prognostication. Examples for predictive biomarkers are methylation of the O-6-methylguanine-DNA methyltransferase (MGMT) promoter and the codeletion of chromosome arms 1p and 19q (1p/19q codel). The autoactive, truncated form of epidermal growth factor receptor (EGFRvIII) and the R132H mutation of isocitrate dehydrogenase 1 (IDH-1) are used as targets in currently running immunotherapeutic, targeted trials. Integration of functional imaging parameters into the monitoring and development of uniform assessment criteria improve the ability to evaluate therapy response and implement imaging biomarkers to guide therapies. As a result of the current efforts there are better classified prognostic groups and improved survival times with maintained functional and quality of life parameters in some glioma subgroups. Given the current dynamics, an improved, better differentiated classification of brain tumors including molecular parameters as well as more rational precise guiding of therapies with early, uniform response assessment is expected in the near future.